Evaluation of Thyroid Dysfunction among VVV College Adopted Village Population, Virudhunagar District (South Indian) - P. Veeramuthumari; R. Aishwarya; I. Pavithra; R. Sangavi (International Journal of Pharma and Bio Sciences, 2021)
In India, one in ten people have recently affected by thyroid dysfunctions such as hyper and hypothyroidism. Several literature studies also reported that women in the age group of 60 have more likely to have hypothyroidism. Many researchers found that iodine deficiency and environmental factors are also play an important role in hypothyroidism and further analyzed about the environmental factors such as exposure to cyanogenic compounds, serious impact on iodine metabolism. This is due to unregulated use of pesticides which leads to endocrine disruptors. Contaminated drinking water and industrial pollutants also causes thyroid dysfunction among the human population those who are living in the contaminated area. The community study assesses that the correlation between the environmental pollution and thyroid hormones level abnormalities among the college adopted village population (K. Usilampatti, Sathiraretiyapatti, Pavali, Meenakshipuram, Sivagnanapuram and Chinnamoopanpatti, Virudhunagar district). The contamination/environmental pollution calculated by collecting the plastic bags in village and sanitation process using questionnaire by the NSS volunteers and authors. Then the information collects through the questionnaire investigated and tabulated as the data. The data subjected to statistical analysis. The significant difference have also found by student t-test. During the survey, we found that various environmental pollution have the main cause of hypo and hyper thyroidism. It leads to infertility in women. Our study found that only during community work in the college adopted villages, the authors reveal that various pollution which might be the main cause of hypo and hyper thyroidism leads to infertility in women. Our work discovers that the prevalence of subclinical hyperthyroidism, hypothyroidism and subclinical hypothyroidism is higher when compares to hyperthyroidism in females than males. This is due to an environmental pollution caused by poor sanitation in villages.